Kontaminasi Logam Berat di Kawasan Pesisir Tanjung Selor Kalimantan Utara - Tri Muji Susantoro; Ariani Andayani (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Heavy Metal Contamination in the Coastal Area of Tanjung Selor North Kalimantan. The establishment of the North Kalimantan Province transformed the Tanjung Selor region and its surroundings into the provincial capital so that it will grow rapidly, both in terms of development and other activities. Monitoring environmental conditions, one of which is heavy metals in the waters need to be carried out as a starting environment before the area develops. This is important given the nature of heavy metals that change toxic at concentrations that exceed the threshold. The purpose of this study is to identify the potential for heavy metal contamination in the coastal area of Tanjung Selor, Bulungan Regency, North Kalimantan Province. Heavy metals studied is limiting to mercury (Hg), Chromium (Cr), Arsenic (As), Cadmium (Cd), Copper (Cu), Lead (Pb) and Zinc (Zn). The location of the sampling was carried out using Landsat 8 imagery designed to represent the condition of the coastal area. Samples come from well water, river water, seawater, and marine sediments at 4, 9 and 5 observation stations respectively. Samples were taken on August 2014 using the grab sample method and analyzed for heavy metal content using the standard American Public Health Association (APHA) method with the Atomic Absorption Spectroscopy (AAS) instrument. Of the 23 samples produced, only 3 observation stations were not contaminated with heavy metals. While in the other 20 samples one of three types of heavy metals were found that exceeded the threshold. In general, Cu is the most detected metal exceeding the threshold in the study area found in samples of river water, sea water and sediment. Zn is found to exceed the threshold in well water. Pb is found to exceed the threshold in sample 5 of river water. Cd is found to exceed the threshold in samples of river water, sea water and sediment. The source of pollution is thought to originate from coal mining activities, oil palm plantations, and household waste. The overall results of this study show that river estuaries tend to accumulate heavy metals.